2013
DOI: 10.1186/1810-522x-52-17
|View full text |Cite
|
Sign up to set email alerts
|

Copepods associated with the red king crab Paralithodes camtschaticus (Tilesius, 1815) in the Barents Sea

Abstract: Background: There are no data on copepod occurrence, infestation indices, and localization on red king crabs in the Russian part of the Barents Sea. For this reason, we examined the species composition, infestation indices, and localization patterns of copepods colonizing the red king crab Paralithodes camtschaticus in Dalnezelenetskaya Bay, a small gulf in the Barents Sea. Results: In total, nine species of Copepoda were found on hosts in July of 2009~2011. Typical planktonic copepods (Calanus, Microsetella, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…In terms of CW sizes, both male and female L. politum were evenly sized at earlier stages of gonadal development (IM and INT A). Dvoretsky and Dvoretsky, (2014) on red king crab Paralithodes camtschaticus suggested that at the earlier stages, sizes were the same between both males and females until reproductive age but in a recent study both male and female L. politum were showing significant differences in size after reaching INT B and DE stages. This study showed females were to be bigger than males after reaching INT B stage and this might due to the extension from gonadal development and external surface for carrying eggs on the abdominal pleopods which means larger berried female crabs with greater volume of eggs as being observed in Liocarcinus depurator (Rufino et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In terms of CW sizes, both male and female L. politum were evenly sized at earlier stages of gonadal development (IM and INT A). Dvoretsky and Dvoretsky, (2014) on red king crab Paralithodes camtschaticus suggested that at the earlier stages, sizes were the same between both males and females until reproductive age but in a recent study both male and female L. politum were showing significant differences in size after reaching INT B and DE stages. This study showed females were to be bigger than males after reaching INT B stage and this might due to the extension from gonadal development and external surface for carrying eggs on the abdominal pleopods which means larger berried female crabs with greater volume of eggs as being observed in Liocarcinus depurator (Rufino et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
“…In crustaceans, the size between males and females might be different after reaching maturity. This might due to the sexual dimorphism, competition for mate and territory (Christy, 1987;Saher & Qureshi, 2012;Dvoretsky & Dvoretsky, 2014). Whilst, another null hypothesis had been raised concerning the size of males and females L. politum after reaching maturity; H 0 = Size between males and females L. politum after passing juvenile stage are equal.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…(Hydrozoa), and Circeis armoricana (Polychaeta). Symbiotic species include Ischyrocerus commensalis and I. anguipes (Amphipoda), Tisbe furcata (Copepoda), Harmothoe imbricata (Polychaeta), and Johanssonia arctica (Hirudinea) (Dvoretsky and Dvoretsky 2009a, 2010a, 2013a. All species found on the crabs appear to be native to the Barents Sea (Dvoretsky and Dvoretsky 2009b, c).…”
Section: Red King Crabmentioning
confidence: 95%
“…El porcentaje de epibiosis fue estimado contabilizando el número de centollones con presencia del anfípodo, además de determinar el número de anfípodos presentes en cada ejemplar (Tabla 1). Estos índices son equivalentes al porcentaje de prevalencia (proporción de P. granulosa con epibiosis) y la intensidad (número de C. ungulina presente en cada ejemplar de centollón) (Bush et al 1997;Dvoretsky & Dvoretsky, 2013). …”
Section: Determinación De Epibiosis Y Localización De C Ungulina En unclassified
“…El porcentaje de epibiosis determinado en el presente estudio es bajo dado que menos del 15% de los ejemplares de P. granulosa analizados mostró epibiosis por parte de C. ungulina (Tabla 1), tomando en consideración el tamaño muestreal y que en otras especies de litódidos introducidos al Mar de Barents (Paralithodes camtschaticus), algunos anfípodos invasores (género Ischyrocerus) muestran niveles de prevalencia sobre el 40% (Dvoretsky & Dvoretsky, 2010) y en especies de copépodos harpacticoídeos comensales muestran valores superiores al 20% de prevalencia en el sistema branquial (Dvoretsky & Dvoretsky, 2013). Dada la captura de sólo ejemplares machos no se puede predecir qué niveles de epibiosis podrían ser comunes en ejemplares de P. granulosa de sexo femenino.…”
Section: Prevalencia De C Ungulina En P Granulosaunclassified